If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 8)(3x + 5) = 0 Reorder the terms: (8 + 2x)(3x + 5) = 0 Reorder the terms: (8 + 2x)(5 + 3x) = 0 Multiply (8 + 2x) * (5 + 3x) (8(5 + 3x) + 2x * (5 + 3x)) = 0 ((5 * 8 + 3x * 8) + 2x * (5 + 3x)) = 0 ((40 + 24x) + 2x * (5 + 3x)) = 0 (40 + 24x + (5 * 2x + 3x * 2x)) = 0 (40 + 24x + (10x + 6x2)) = 0 Combine like terms: 24x + 10x = 34x (40 + 34x + 6x2) = 0 Solving 40 + 34x + 6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(20 + 17x + 3x2) = 0 Factor a trinomial. 2((4 + x)(5 + 3x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(4 + x)' equal to zero and attempt to solve: Simplifying 4 + x = 0 Solving 4 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4Subproblem 2
Set the factor '(5 + 3x)' equal to zero and attempt to solve: Simplifying 5 + 3x = 0 Solving 5 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = 0 + -5 3x = 0 + -5 Combine like terms: 0 + -5 = -5 3x = -5 Divide each side by '3'. x = -1.666666667 Simplifying x = -1.666666667Solution
x = {-4, -1.666666667}
| 0.5(x+60)+1.3x=111 | | (-1)(-5)(-6)= | | (f)-2=9x^2-5x+2 | | -4(3n+2)-6(5-n)=-32 | | 3x=17x | | 3(2k-1)=-38 | | x^2-20x+24=0 | | 3(4z-1)-4(z+3)=3(z+1) | | 6-2(x+2)=x-18 | | 6=5z+2 | | -3y-18=-12 | | sprt(4x^2)=0 | | 3(4z-1)4(z+3)=3(z+1) | | 6(1+5x)-x=-100 | | 9x+90=6x+120 | | 3x-x*lnx=0 | | Y+2=74 | | 4+3(x-3)=9-7(x-2) | | 14-x=17-8 | | X=1436.31-(0.09*X) | | 4c=0 | | 16x^3+6x^2-8x=0 | | (11-y)-(19+10y)= | | 13x-3y=17 | | 2d^3-5x^2=3x | | 12x+3=6x-10 | | 0.09-X=1436.31-x | | -2.2=2.8-5y | | -3r-2=10 | | (123+456)(147852+369852)=0 | | 5-6x+6+5x+2x-3=1+3*4 | | 11x-x=55-13 |